Comparative Analysis of the Quality of Roll Cake with Different Types of Eggs - Jasmine, Zoya; Siregar, Juliana; Gusnita, Wiwik; Indrayeni, Wiwik (Universitas Negeri Padang, 2025)
This study aims to compare the quality of roll cakes prepared using different types of eggs, namely layer chicken eggs and free-range chicken eggs. Eggs serve as a main ingredient in cake formulation, significantly affecting the physical and sensory properties of the final product. A comparative research design was applied to evaluate two samples under controlled conditions. Sensory evaluation was conducted to assess organoleptic attributes, including shape, volume, color, aroma, texture, and taste. Data were collected from 30 Culinary Arts Students. Data were analyzed using the t-test (independent sample t-test) to determine whether there were significant differences between the two treatments. The results showed that roll cakes made with local chicken eggs had a larger diameter, a brighter yellow inner color, a more pleasant aroma, and a softer texture compared to those made with layer chicken eggs. The t-test revealed significant differences in shape, inner color, texture, and taste, while volume, crust color, and aroma showed no significant difference